URGENSI MODAL SOSIAL DALAM LIBERALISASI PEREKONOMIAN BAGI USAHA KECIL MENENGAH DI INDONESIA - Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Trade liberalization influences small industries in Indonesia. This happens because of the high overheadcost, minimum technology, limited financial capital, and competitive and efficient marketing network. In order to overcome this problem, there must be tangible steps to reinforce the financial capital and other sectors for the small industries in Indonesia. One of the steps is reinforcing the social capital as the network and marketing reinforcement. Some researches stated that social capital is the efficient and effective means in reinforcing the existence of UMKM in Indonesia to face global trading.